Atrichum laoshanense Y.-J.Yi & S.He, a new species of Polytrichaceae from eastern China. (2nd October 2015) - Yi, Yan-Jun; He, Si
Abstract : Atrichum laoshanense Y.-J.Yi & S.He, a new species of Polytrichaceae from Laoshan mountain in Shandong Province, eastern China, is described and illustrated. The new species resembles, and is related to A. angustatum (Brid.) Bruch & Schimp., but differs in the presence of stellately papillose median leaf cells, multicellular laminal teeth with well-defined outgrowths of pedestal cells on the distal dorsal lamina, and papillose stem epidermal cells. An updated key to species of Atrichum in China is presented.